(untitled) (Journal of Educational Sciences, 2026)
The article addresses the problem of forming AI-based professional competence of pre-service English language teachers in the context of educational digitalization in the Republic of Kazakhstan. The aim of the study is to experimentally substantiate the pedagogical conditions, methods and effectiveness of developing AI competence among the pre-service teachers. The research employed a complex of methods including theoretical analysis, questionnaire survey, observation, expert evaluation, pedagogical experiment and mathematical statistics. The study was conducted at M.Auezov South Kazakhstan University and South Kazakhstan pedagogical university named after O. Zhanibekov. The participants included third-year students enrolled in the educational program Foreign Language: two foreign languages, as well as university instructors. In total, 148 students took part in the study (control group-76 students; experimental group -72 students), along with 27 teachers. During the formative stage, the experimental group systematically implemented AI-based pedagogical technologies, including AI-supported flipped classroom, project-based learning, microteaching with AI feedback, learning analytics and automated assessment. The results demonstrated a statistically significance increase in the high and sufficient levels AI competence in the experimental group, while no substantial changes were observed in the control group. The findings that AI-based professional competence does not develop spontaneously but requires purposeful and systematic pedagogical intervention. The results of the study provide a basis for developing practical recommendations aimed at improving the content of pre-service English teacher education and integrating digital pedagogical technologies into educational process. Keywords: artificial intelligence, educational digitalization, pre-service English language teacher, professional competence, AI competence, digital pedagogy.